Strangers in Paradise : Contemporary Australian Art to Korea. (Seoul : The National Museum of Contemporary Art, 1992)
Bennett, Gordon ; Callas, Peter ; Carchesio, Eugene ; Gillies, John and the Sydney Front ; Henson, Bill ; Hill, Michael ; Laing, Rosemary ; Lee, Lindy ; Nixon, John ; Norrie, Susan ; Onus, Lin ; Rrap, Julie ; Scott, Jill ; Stacey, Robyn ; Unsworth, Ken
Strangers in Paradise : Contemporary Australian Art to Korea, The National Museum of Contemporary Art, Seoul, 05.11. - 04.12.1992
boek
Keywords: Australië